3-MINUTE THESIS COMPETITION: THE S.O.P. FOR SUCCESS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 13 April 2016 An annual academic competition, the 3Minute Thesis Competition (3MT), organised by the Universiti Sains Malaysia (USM) Institute of Postgraduate Studies (IPS) would assist the currentlyenrolled postgraduate students to develop effective presentation and communication skills.